High-through identification of T cell-specific phage-exposed mimotopes using PBMCs from tegumentary leishmaniasis patients and their use as vaccine candidates against Leishmania amazonensis infection. Issue 3 (10th September 2018) - Carvalho, Gerusa B.; Costa, Lourena E.; Lage, Daniela P.; Ramos, Fernanda F.; Santos, Thaís T. O.; Ribeiro, Patrícia A. F.; Dias, Daniel S.; Salles, Beatriz C. S.; Lima, Mariana P.; Carvalho, Lívia M.; Dias, Ana C. S.; Alves, Patrícia T.; et al.
Abstract: In the current study, phage-exposed mimotopes as targets against tegumentary leishmaniasis (TL) were selected by means of bio-panning cycles employing sera of TL patients and healthy subjects, besides the immune stimulation of peripheral blood mononuclear cells (PBMCs) collected from untreated and treated TL patients and healthy subjects. The clones were evaluated regarding their specific interferon- γ (IFN- γ ) and interleukin-4 (IL-4) production in the in vitro cultures, and selectivity and specificity values were calculated, and those presenting the best results were selected for the in vivo experiments. Two clones, namely A4 and A8, were identified and used in immunization protocols from BALB/c mice to protect against Leishmania amazonensis infection. Results showed a polarized Th1 response generated after vaccination, being based on significantly higher levels of IFN- γ, IL-2, IL-12, tumour necrosis factor- α (TNF- α ) and granulocyte-macrophage colony-stimulating factor (GM-CSF); which were associated with lower production of specific IL-4, IL-10 and immunoglobulin G1 (IgG1) antibodies. Vaccinated mice presented significant reductions in the parasite load in the infected tissue and distinct organs, when compared with controls. In conclusion, we presented a strategy to identify new mimotopes able to induce Th1 response in PBMCs from TL patients and healthy subjects, and that were successfully used to protect against L. amazonensis infection.